Saúde mental do trabalhador e da trabalhadora da saúde em hospital do Ceará: avaliação sobre o cuidado de quem cuida - Silva, Antonia Eline Lopes da (2024)
This research aimed to evaluate mental health actions directed at healthcare workers in a Mental Health Hospital in Fortaleza, Ceará, and specifically: i) to characterize the work environment of the hospital, highlighting the general working conditions, food and rest spaces; ii) to identify the actions developed by the hospital unit for the mental health care of its workers; and iii) to understand the meanings of these actions for the workers of the service in question. This is an exploratory research, based on the theoretical and methodological bases of in-depth evaluation, with a qualitative approach. The subjects were health professionals and healthcare workers of a Mental Health Hospital in Ceará and the unit manager. For data collection and registration, a semi-structured interview script was used, with digital media recording, respecting ethical issues. In data analysis, the Content Analysis tool was used, as it is an instrument with a variety of forms and appropriate for qualitative and evaluative research using interviews and documentary data. Regarding the results presented, it is noteworthy that 13 people were interviewed, six of whom were male and seven female. Regarding age, among the interviewees aged 18 to 29 and 50 to 69, there were four in each age group and five were in the age range between 30 and 49 years. Most interviewees highlighted negative aspects related to the service infrastructure. In general, the interviewees positively assessed their current health condition. The situation of multiple ties and, even more so, precarious ties were also identified in the research. Of the 13 interviewees, including the manager, 10 workers were affiliated with the hospital through a cooperative. The main reasons for leave were respiratory symptoms. The interviewees worked at the Mental Health Hospital because they identified with the work done in mental health. Issues such as anxiety, demotivation, feelings of incapacity, and stress were highlighted. Regarding mental health actions, for the workers, these were incipient and did not effectively guarantee the health and safety conditions of the workforce. Thus, there are various forms of work that exploit these workers to the limit of their bodies and minds. It is known that work can generate well-being as an activity that builds and gives meaning to human beings. However, in modern capitalist societies, it is more common for work to generate illness and suffering, especially mental suffering, even if, in general, workers themselves do not perceive themselves as ill or suffering, and this is due to a variety of related factors, especially work relationships, the imposition of accelerated rhythms and insufficient remuneration, and working conditions that compromise the power of work and its safety and quality, particularly in the field of health and mental health.